The Effect of Residual Stress on the Electromechanical Behavior of Electrostatic Microactuators - Ming-Hung Hsu (Active and Passive Electronic Components)
This work simulates the nonlinear electromechanical behavior of different electrostatic microactuators. It applies the differential quadrature method, Hamilton's principle, and Wilson-θ integration method to derive the equations of motion of electrostatic microactuators and find a solution to these equations. Nonlinear equation difficulties are overcome by using the differential quadrature method. The stresses of electrostatic actuators are determined, and the residual stress effects of electrostatic microactuators are simulated.